Pengaruh Kinerja Keuangan Dan Inflasi Terhadap Return On Asset Pada Bank Umum Syariah Di Indonesia - Idris Saleh (LPPM ISNJ Bengkalis, 2021)
This research aims to show the effect of capital adequacy ratio (CAR), financing to deposit ratio (FDR), non-performing financing (NPF), operating expenses on operating income (OEOI), and inflation partially and simultaneously on return on assets (ROA) at Sharia Commercial Bank in Indonesia. This type of research is a quantitative research using secondary data based on panel data. The research population consisted of 11 Islamic Commercial Banks in Indonesia using the purposive sampling technique so that 220 samples were obtained. The data analysis technique used is panel data regression method, classical assumption test, coefficient of determination, t-test, and f-test. The results show that CAR has a positive and significant effect on ROA, FDR has a negative and insignificant effect on ROA, NPF, and inflation has a positive effect and is not significant on ROA. At the same time, OEOI has a negative and significant effect on ROA. Simultaneously all independent variables have a significant effect on ROA.